Experimental study on co-combustion of low rank coal semicoke and oil sludge by TG-FTIR. (October 2020) - Zhao, Ruidong; Qin, Jianguang; Chen, Tianju; Wang, Leilei; Wu, Jinhu
Highlights: Co-combustion is proposed as an effective co-disposal mode for LRCS and oil sludge. Combustion and kinetic performance are improved with proper addition of oil sludge. The maximum activation energy is obtained at conversion rate range of 0.4. LRCS has suppression effect on NOx emission while oil sludge is just the opposite. Co-combustion can reduce SO2 emission due to low sulfur release rate of oil sludge. Abstract: Co-combustion was proposed as an effective and complementary means for the co-treatment of low rank coal semicoke (LRCS) and oil sludge. The combustion, kinetics and gaseous pollutants emission characteristics during co-combustion of LRCS and oil sludge were investigated by thermogravimetric analyzer coupled with Fourier transform infrared spectrometer (TG-FTIR). Results showed oil sludge had more complex weight loss characteristics than LRCS. Proper addition of oil sludge could effectively improve the ignition, burnout and comprehensive combustion performance of blends and 60% was a recommended oil sludge blend ratio. High heating rates could also enhance the combustion performance of blends. The activation energy determined by Coats-Redfern method gradually decreased with the increase of oil sludge blend ratio. DAEM kinetic analysis results showed the maximum activation energy of 113.4 kJ/mol was obtained when conversion rate was 0.4 due to the poor ignition performance of LRCS. All of the CO, CO2, NOx and SO2 emission gradually decreased with the increasing oil sludge blend ratio. LRCS had suppression effect on NOx emission during co-combustion while oil sludge was just the opposite. The low sulfur release rate of oil sludge resulted in the decreasing SO2 emission of blends although oil sludge had promotion effect on SO2 emission.